The Relationship Between Knowledge, Nutritional Status and Anemia in Adolescents in Bulukumba Regency - Jusni Jusni; Arfiani Arfiani; Husnul Khatimah; Kurniati Akhfar; Rahmaniyah R (Proceeding of the International Conference on Health Sciences and Nursing, 2025)
Anemia is a global health problem, particularly affecting adolescent girls due to their increased iron needs during growth and menstruation. In Indonesia, the prevalence of anemia among adolescents reaches 32%, posing risks such as fatigue, decreased concentration, stunted growth, and lowered immunity. Poor nutritional status and lack of knowledge are suspected to contribute to anemia in this group. Objective:This study aims to determine the relationship between nutritional status and knowledge level with the incidence of anemia among adolescents at the Tahirah Al Baeti Bulukumba Midwifery Academy.Methods: This was a quantitative descriptive study involving 10 adolescent girls with anemia, selected through total sampling from a population of 27 students. Data were collected using questionnaires and BMI measurements. Statistical analysis was performed using the Chi-square test to assess the relationship between variables.Results: Of the 10 respondents, 6 (60%) experienced mild anemia and 4 (40%) experienced severe anemia. There was a significant relationship between nutritional status and anemia incidence (p = 0.004); all respondents with normal BMI experienced only mild anemia, while 80% of those with abnormal BMI suffered from severe anemia. However, the relationship between knowledge level and anemia incidence was not statistically significant (p = 0.548). Conclusion: Nutritional status significantly affects the incidence and severity of anemia among adolescent girls, with those having abnormal BMI at greater risk. In contrast, knowledge level alone does not significantly influence anemia occurrence. Therefore, improving adolescent nutrition should be prioritized, while educational programs should continue to support healthier behavior and anemia prevention.